Urgent Considerations on the Relationship Between the Advance of Covid-19 in Indigenous Territories in Brazil and the Impacts of Monoepistemic Public Policies - Herbetta, Alexandre; Pocuhto, Taís; Pimentel Da Silva, Maria do Socorro; Guajajara, Cintia (Frontiers in Sociology, 2021)
The following text seeks to deal initially, but according to the urgency of the topic, on the advance of Covid-19 in indigenous territories in Brazil, whether urban or rural. Firstly, through a brief analysis of the Brazilian government's indigenous policies, which will take place through the comparison of bulletins and data from the Special Secretariat for Indigenous Health (SESAI), an agency linked to the Ministry of Health (MS) and data from the Articulation Indigenous Peoples of Brazil (APIB), the main Brazilian indigenous political movement. Then, we will systematize strategies developed and executed by some indigenous populations in Brazil, which will be carried out through an exploratory analysis of manifestations of indigenous leaders on the Internet, actions in the legal sphere, as well as actions in the territory. Finally, we problematize the monoepistemic character of public policies on the issue.